Oral Immunization of Macaques with Attenuated Vaccine Virus Induces Protection against Vaginally Transmitted AIDS - Joag, Sanjay V. (American Society for Microbiology (ASM), 1998)
The chimeric simian-human immunodeficiency virus SHIV(KU-1), bearing the envelope of human immunodeficiency virus type 1 (HIV-1), causes fulminant infection with subtotal loss of CD4(+) T cells followed by development of AIDS in intravaginally inoculated macaques and thus provides a highly relevant model of sexually transmitted disease caused by HIV-1 in human beings. Previous studies using this SHIV model had shown that the vpu and nef genes were important in pathogenesis of the infection, and so we deleted portions of these genes to create two vaccines, ΔvpuΔnefSHIV-4 (vaccine 1) and ΔvpuSHIV(PPc) (vaccine 2). Six adult macaques were immunized subcutaneously with vaccine 1, and six were immunized orally with vaccine 2. Both viruses caused infection in all inoculated animals, but whereas vaccine 1 virus caused only a nonproductive type of infection, vaccine 2 virus replicated productively but transiently for a 6- to 10-week period. Both groups were challenged 6 to 7 months later with pathogenic SHIV(KU-1) by the intravaginal route. All four unvaccinated controls developed low CD4(+) T-cell counts (<200/μl) and AIDS. The 12 vaccinated animals all became infected with SHIV(KU-1), and two in group 1 developed a persistent productive infection followed by development of AIDS in one. The other 10 have maintained almost complete control over virus replication even though spliced viral RNA was detected in lymph nodes. This suppression of virus replication correlated with robust antiviral cell-mediated immune responses. This is the first demonstration of protection against virulent SHIV administered by the intravaginal route. This study supports the concept that sexually transmitted HIV disease can be prevented by parenteral or oral immunization.